2022
DOI: 10.3389/frobt.2021.748853
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Hearing Sensitivity Affect Robot-Based Training for Children Diagnosed With Autism Spectrum Disorder

Abstract: In this paper, we investigate the impact of sensory sensitivity during robot-assisted training for children diagnosed with Autism Spectrum Disorder (ASD). Indeed, user-adaptation for robot-based therapies could help users to focus on the training, and thus improve the benefits of the interactions. Children diagnosed with ASD often suffer from sensory sensitivity, and can show hyper or hypo-reactivity to sensory events, such as reacting strongly or not at all to sounds, movements, or touch. Considering it durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We believe it is relevant to report that one study indicated an association between severity and stimulus preference (Ali et al, 2021). Stimulus preference has also been linked to perceptive sensitivity, as demonstrated by two studies involving children, showing that perceptive sensitivity influences the interaction with the robot and the outcomes of the robot-mediated intervention (Chevalier et al, 2022). Kumazaki and colleagues (2022a) also indicated that sensory sensitivity affects the interaction with the robot, even in older participants and adults.…”
Section: Evidence From Experimental Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…We believe it is relevant to report that one study indicated an association between severity and stimulus preference (Ali et al, 2021). Stimulus preference has also been linked to perceptive sensitivity, as demonstrated by two studies involving children, showing that perceptive sensitivity influences the interaction with the robot and the outcomes of the robot-mediated intervention (Chevalier et al, 2022). Kumazaki and colleagues (2022a) also indicated that sensory sensitivity affects the interaction with the robot, even in older participants and adults.…”
Section: Evidence From Experimental Studiesmentioning
confidence: 95%
“…Sensitivity to vision is linked to improved joint attention skills in children with ASD during robot-assisted therapy, especially for those with lower visual sensitivity. Conversely, higher sensitivity to hearing is associated with better outcomes when combining standard therapy with robot activities, potentially due to heightened responsiveness to the robot's motor sounds (Chevalier et al, 2022).…”
Section: Aspects Related To the Asd User Influencing The Interactionmentioning
confidence: 99%
“…However, the usefulness of ER extends beyond mathematical, logical and computational thinking. Different studies [10][11][12][13][14][15][16] agree that robot-supported interventions can be particularly useful as an educational strategy for students with neurodevelopmental disorders, such as attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and developmental language disorder (DLD). And this is so not only at an educational strategy level, but also as part of therapeutical protocols [17].…”
Section: Introductionmentioning
confidence: 99%